Geomorfologia e neotectônica da bacia do rio Cauamé - Reis Neto, Raimundo Alves dos (2007)
This study had as objectives to identify and to analyze the geomorphology and neotectonic in Cauamé River basin, tributary of the right bank of Branco River, located in the municipalities of Boa Vista and Alto Alegre – Roraima, Brazil. To the attainment of data were used several equipments, collection of information and field activities, processing and integrated analysis of the geological and geomorphological characteristics, soil and vegetation where visual interpretation methods (photo interpretation) and digital treatment of orbital image were used. Cauamé River, whose basin drains different geomorphological surfaces, is based by Mesozoic and cenozoic rocks pré-Cambrian of Craton Guianês with geological structure composed by the Group Surumu, Volcanic Complex Apoteri, Group Cauarane, Metamorphic Suite Urubu River and Boa Vista Formation. About the “pedologia”, they stand out Oxisols and Ultisols; in wavy areas, prevail the Entisols Troporthents and, in the hollow, Hydromorphic “Neossolos” Quartzipsamments. The climate is of the Awi type, with two well defined stations, where it predominate the savanna vegetation with different characteristics. Six geomorfológicas units had been identified: Plains and fluvial terraces of the river bigger Cauamé and “igarapés”; Residual Inselbergs and remainders; Subject to flooding wavy areas, trails and lakes; Hills and morrotes of the high and average Cauamé Layers of inter-area Cauamé-Uraricoera and of Boa Vista depression. The presence of flaws promotes, partly, the direction of the drainage that follows preferencially the directions NE-SW (influenced by the hemigráben of Tacutu) and NW-SE, with the control of the drainage of the river. Five patterns of drainage were individualized: dendritic, subrectangular, subdendritic with rectangular component, parallel and directional trellis. The hydrography conditions and relief point indications of recent tectonics moving, whose evidences asymmetry of drainage, rapids, anomalous curves and drainage captures. The largest urban concentration of the basin happens in the city of Boa Vista, installed in Boa Vista Depression domains. The morphometrics parameters demonstrate that the basin is inserted in an area of 3190Km2, it presents rectangular form, drainage of 7th order, the length of the main channel is of 120, 2 km, with density of low drainage. It indicates that the basin is not disposed to floods.